Copro-prevalence of Cystoisospora spp. in domestic dogs (Canis lupus familiaris) in Cajamarca district, Peru. - Bacilio-Gutiérrez, D. (2023)
Cystoisosporosis is the infection produced by a coccidian that invades the digestive tract causing severe anatomopathological disorders in the infected vertebrate. This parasitosis is neglected or underes-timated in dogs in the Cajamarca region, Peru. The objective of the present study was to determine the copro-prevalence of Cystoisospora spp. and its oocyst morphometry in dogs from the western zone of the district of Cajamarca. Using the Faust method, 246 fecal samples were analyzed from dogs with owners of both sexes, divided into three age group (n=87 puppies: 0 to 6 months, n=43 juvenile: 6 to 12 months, and n=166 adults: > 12 months). The results showed an overall prevalence of 15.04% for Cystoisospora spp. of which 24.14% corresponded to the puppies, 20.93% to juveniles, and 6.03% to dogs older than 12 months. The oocysts observed presented yellowish green color, with the absence of micropyle and ovoid shape di-vided into two groups, the first with 36.63 ± 5.05 by 35.90 ± 7.71 μm and the second with 38.54 ± 4.38 by 33.74 ± 4.15 μm. It is concluded that the prevalence of Cystoisospora spp. is low, with a higher presence in puppies, which decreases with age. In addition, according to its morphometric characteristics, it would be C. canis, which requires molecular studies for its definitive identification.